Terapi Bermain Clay Terhadap Anxiety Anak Akibat Hospitalisasi di Magetan - Lailaturohmah Kurniawati; Deby Putri Angela; Dea Kusuma Rahmawati (Panggung Kebaikan : Jurnal Pengabdian Sosial, 2025)
Children often experience feelings of discomfort, anxiety and anxiety when undergoing treatment at the hospital, and some are even traumatized by medical actions. Clay play therapy is an alternative therapy that can reduce children's anxiety. Play therapy using clay involves shaping or making various shapes/characters from clay (plasticine). Objective; Reducing children's anxiety due to hospitalization with Clay Therapy. Methods: The methods used in Community Service are the Preparation Stage, Implementation Stage, and Evaluation Stage. Results: There is a significant increase in changes in anxiety levels with 95% of children experiencing mild anxiety after playing clay therapy. Conclusion: There is a Significant Impact of Clay Play Therapy on Children's Anxiety Due to Hospitalization in the Hospital.